Promoting of Maternal Role Attainment Achievement in Adolescent Mothers: A Case Study in Nakhon Phanom Province - อินทรเกษม ศิริรัตน์; สินธุศิริ พยอม; สวัสดิโชตติ์ ดารุนนีย์; โคตรพรม จรินทร; ไชยวาน วรนุช (Journal of The Royal Thai Army Nurses, 2019)
This Retrospective cohort study aimed to study 1) impacts of maternal and problems of maternal role attainment in adolescent mothers 2) factors affecting maternal role attainment achievement in adolescent mothers and 3) develop direction of promoting maternal role attainment achievement in adolescent mothers. The samples consisted of 507 adolescent mothers who aged 15-19 years and labored at Nakhon Phanom hospital in 2016. Data collected by using personal data form and Maternal and Child health data record that researcher developed from literature review. The data were analyzed by using frequency, percentage, mean, standardized deviation, independent t-test and multivariable risk regression. The results of this study demonstrated that the impact of adolescent mothers comprised of severe preeclampsia, hematocrit level was less than 33 percent, Postpartum Hemorrhage, premature labor, and low birth weight newborn that weight less than 2,500 grams. The highest factors affecting maternal role attainment achievement was family support (p = .002), newborn’s birth weight were normal (p = .001), and newborn who have non-complication (p = .027), respectively. In addition, the result of this study showed that directions of promoting maternal role attainment achievement comprised of 1) finding out/seeking key person in their family who influenced adolescent mothers when the first time of adolescent mothers’ Antenatal Care (ANC), 2) preparing of adolescent mothers when they were during the antenatal period and health care providers provide home visit during the postpartum period, 3) preparing of family members’ adjustment on changes in their family, 4) continuously follow up and provided mental health care by mental health care providers, and 5) continuously giving health care informations that focused on child rearing skills and evaluated adolescent mothers’ maternal role attainment by health care providers. Conclusion and recommendations based on the findings of this study, It is recommended that health care providers and related personnel should utilize these findings for enhancing effectiveness and efficiency of planning, adjustment strategies, and developing model or guideline or promoting program/activities that appropriate for context clue in each area.